Pengembangan Bahan Ajar Muatan Lokal Berbasis Seni Rupa Lokal di Sekolah Menengah Pertama - Tangsi Tangsi; Sofyan Salam; A. Jamilah (Seminar Nasional LP2M UNM, 2019)
Abstract. This study aims to develop a Local Content teaching material based on local art. This study follows the procedure for developing the Richey Model Instructional System Design which consists of 6 stages. But in this study only reached stage 4. Development of teaching materials begins with needs analysis. From the needs analysis, it is designed local content learning materials based on local art which contain subject matter, learning objectives, and evaluation tools for learning outcomes equipped with assessment indicators. The initial design of Local Content teaching materials based on local art was validated and validated by material experts and the graphics of competent lecturers. In addition to the validation of the lecturers, several Cultural Arts teachers also provided input on the teaching materials that had been developed. Suggestions for material content validators are language adjustment with target users, enriching material, and clarifying images. While the general correction is typing errors. Suggestions and corrections from the validator are then analyzed by researchers to improve teaching materials developed. After the design of teaching materials is improved based on input from the validator, the local art-based local content teaching materials developed have been considered valid and ready to be tested in the field. Keywords: Teaching materials, local content, local art